THE ROLE OF BANKING IN PAYMENT OF INTERNATIONAL TRADE CONTRACT - Muhammad Sood (Jurnal IUS Kajian Hukum dan Keadilan, 2018)
The research aims to find out the regulation of Letter of Credit (L/C) as an instrument of payment in international trade; and to analyze the role of banks inthe implementation of payment services in international trade contracts. This research is a normative legal research with statutory approach, dan conceptual approach. The technique of collecting legal material is done by literature study, analyzing various legal references relevant to the examined issues to be further analyzed qualitatively and descriptively. It conducted by applying in depth and holistic review of the various references, and evaluated the legal materials as regulatory description of the role of banks in international trade contracts. The results of research indiceted that, the L/C regulation as a instrument of payment, regulatedin the International Civil Law (ICL) and in the Uniform Custom and Practice (UCP) provisions. According to ICL, the relations of the parties in trade contract based on the agreed legal option. If there is no legal option, it refers to the principle of the most characteristic performance, refers to the country in which the bank gives credit, or in which country the credit is disbursed. As for itsregulation in UCP 600, that L/C is an agreement requiring a bank to act upon request and instruction from a customer to conduct payment to the beneficiary. Meanwhile the role of banks in the implementation of payment services in international trade contracts is to guarantee payment of goods thatsent by exporters to importers in accordance with agreed price, and to ensure completeness of the shipment documents.